What’s the tea, honey?: uma análise das performatividades drag queen no Instagram - Almeida, Raffael Bezerra (2024)
This study intends to analyze the artistic activity of three drag queens from the city of Fortaleza having the performance studies as basis and with an emphasis on the use of social media as a platform for the dissemination of their artistic works on the chosen digital social network, which is Instagram. It also has the participation of three national drag queens whose performativity on Instagram is going to be analyzed. It is understood by performativity, although the word itself is not attested in the Portuguese Orthographic Vocabulary (whether in the Brazilian Academy of Letters or in the Portuguese Language Portal), it is part of the lexicon of performing arts, or that is, arts that involve a bodily action by the artist, usually on a stage in front of an audience, such as theater, dance, circus, also called scenic arts because they usually develop in a scene, that is, on a stage. This research also proposes to describe the mechanisms of the application that act as a reference for drag participants in the study, both internationally and nationally. This work aims to understand and describe the construction of the imagery and performance narrative of the participating drag queens, three of them from the city of Fortaleza (@supremmas, @aurineidecamurupim, @mulherbarbadaoficial) and three of national reach (@xuxameneghel, @rita_von_hunty, @pabblovittar). The methodological proposal of this research focuses on the description and analysis of the relevance of the digital social network Instagram for the formation of its characters and how engagement in it happens.